Jan Lechoń: wiatr nocy, rysunek rdzy (na marginesie wiersza Stara Warszawa) - Próchniak, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2010)
The present sketch proposes an aspectual analysis and interpretation of the poem Stara Warszawa by Jan Lechoń. The author of the sketch is interested in architectonics of the world revealed and rendered in the poem, in a complex and intricate network of relations in which the poem establishes, maintains, develops and interacts with other cultural texts, as well as its existentialist dimension. The basic frame of reference for the last mentioned issue is the friendship shared by Lechoń and Stanisław Baliński.